2016
DOI: 10.1093/mutage/gew030
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of TiO2nanoparticles assessed by mini-gel comet assay and micronucleus scoring with flow cytometry

Abstract: The widespread production and use of nanoparticles calls for faster and more reliable methods to assess their safety. The main aim of this study was to investigate the genotoxicity of three reference TiO2 nanomaterials (NM) within the frame of the FP7-NANoREG project, with a particular focus on testing the applicability of mini-gel comet assay and micronucleus (MN) scoring by flow cytometry. BEAS-2B cells cultured under serum-free conditions were exposed to NM100 (anatase, 50–150nm), NM101 (anatase, 5–8nm) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 37 publications
7
73
0
Order By: Relevance
“…For micronucleus analysis, 2% phytohemagglutinin (Murex, Dartford, Kent, UK) was added to stimulate lymphocyte proliferation. To reduce the TiO 2 photocatalytic activity (Di Bucchianico et al, ) that can create extracellular ROS, we kept particle suspensions and PBMC cultures after treatment, in dark conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For micronucleus analysis, 2% phytohemagglutinin (Murex, Dartford, Kent, UK) was added to stimulate lymphocyte proliferation. To reduce the TiO 2 photocatalytic activity (Di Bucchianico et al, ) that can create extracellular ROS, we kept particle suspensions and PBMC cultures after treatment, in dark conditions.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce the TiO 2 photocatalytic activity (Di Bucchianico et al, 2017) that can create extracellular ROS, we kept particle suspensions and PBMC cultures after treatment, in dark conditions.…”
Section: Blood Samples Peripheral Blood Mononuclear Cell Freezingmentioning
confidence: 99%
“…The cells were washed with PBS (Gibco) and harvested with trypsin (Gibco) and then processed for the comet assay. The mini‐gel comet assay as previously described [Di Bucchianico et al, ] was used and cells exposed to hydrogen peroxide (0.05 M) for 5 min on ice were used as a positive control. In short, following exposure, cells were embedded in 1.1% agarose mini‐gels on pre‐coated (0.5% agarose) microscope slides.…”
Section: Pccsmentioning
confidence: 99%
“…Their results, based on DNA damage, mutagenicity, and cancerogenetic potential in mammalian cells, confirmed that ZTA material could be considered suitable for biomedical applications. The addition of titania could induce non-significant genotoxic effects [50][51][52]. However, as observed by Lu et al [53], who studied the effects of titania on the induction of sister chromatid exchanges and micronuclei in Chinese hamster ovary-K1 cells, the titania could have a potentially genotoxic effect.…”
Section: Genotoxicitymentioning
confidence: 98%